Crystal chemistry of zinc incorporation in strunzite-group minerals containing zeolitic water. (2nd January 2018) - Grey, I. E.; Keck, E.; MacRae, C. M.; Glenn, A. M.; Kampf, A. R.; Nash, B. P.; Mills, S. J.
Abstract: A comparative study is presented of the chemistry and crystallography of zinc-bearing strunzites from Hagendorf Süd, Bavaria, Germany and the Sitio do Castelo mine, Folgosinho, Portugal. Electron microprobe analyses of samples from the two localities show quite different cation substitutions. The Hagendorf Süd mineral is a Zn-bearing ferristrunzite, with compositional zoning due to Zn 2+ replacing predominantly Fe 3+ as well as minor Mn 2+, whereas the Portugese mineral is a Zn-bearing strunzite, in which Zn 2+ replaces Mn 2+, with minor replacement of Fe 3+ by Mn 3+ . Zincostrunzite, with dominant Zn in the interlayer octahedrally coordinated site, is a new strunzite-group mineral that has been characterized at both locations. Analysis of single-crystal synchrotron data for zinc-bearing ferristrunzite and zincostrunzite crystals from Hagendorf Süd show that the structures of both minerals contain zeolitic water in the interlayer region. The formula for strunzite-group minerals containing the zeolitic water is M Fe2 3+ (PO4 )2 (OH)2 ·6.5H2 O, M=Fe, Mn, Zn. This formulation agrees with that found for zincostrunzite from the Sitio do Castelo mine, but differs from that reported previously for strunzite, M Fe2 + (PO4 )2 (OH)2 ·6H2 O, which has no interlayer water. Interestingly, the zincostrunzites from the two localities differ in the location of the interlayer water molecule, with a corresponding difference in the H bonding.